2008
DOI: 10.1039/b711199a
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Pb in urine and Cd, Pb, Cu, and Ag in natural waters using electrochemical sensors immobilized with DMSA functionalized magnetic nanoparticles

Abstract: Urine is universally recognized as one of the best non-invasive matrices for biomonitoring exposure to a broad range of xenobiotics, including toxic metals. Detection of metal ions in urine has been problematic due to the protein competition and electrode fouling. For direct, simple, and field-deployable monitoring of urinary Pb, electrochemical sensors employing superparamagnetic iron oxide (Fe3O4) nanoparticles with a surface functionalization of dimercaptosuccinic acid (DMSA) has been developed. The metal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…In addition, none of the described ligands, need to be synthesized as all can be purchased in their usable form. As an example, we have shown that iron oxide nanoparticles stabilized with meso-2,3-dimercaptosuccinic acid (DMSA) make excellent sorbents for toxic heavy metals in a variety of media, [3,4] but literature exists describing antibody conjugation to these same nanoparticles for use in biological systems for separation and detection. [30] Because the orientation of the thiol affinity moiety on the nanoparticle surface can have a significant effect on the binding potential towards a specific heavy metal ion, [31] the use of a variety of thiol-containing ligands allowed us to explore which ligands allowed for maximal analyte binding.…”
Section: Selection Of Magnetic Nanoparticle Sorbent Ligand Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, none of the described ligands, need to be synthesized as all can be purchased in their usable form. As an example, we have shown that iron oxide nanoparticles stabilized with meso-2,3-dimercaptosuccinic acid (DMSA) make excellent sorbents for toxic heavy metals in a variety of media, [3,4] but literature exists describing antibody conjugation to these same nanoparticles for use in biological systems for separation and detection. [30] Because the orientation of the thiol affinity moiety on the nanoparticle surface can have a significant effect on the binding potential towards a specific heavy metal ion, [31] the use of a variety of thiol-containing ligands allowed us to explore which ligands allowed for maximal analyte binding.…”
Section: Selection Of Magnetic Nanoparticle Sorbent Ligand Structuresmentioning
confidence: 99%
“…We have recently shown the efficacy of functionalized iron oxide nanoparticles as both sorbents for a number of toxic heavy metal contaminants in aqueous systems, [3] as well as the sensing element for electrochemical detection of heavy metals in complex sample matrices, for example, contaminated waters and biological fluids. [4] These studies have produced very promising results regarding the potential use of nontoxic, relatively inexpensive, surfacetailored, magnetic iron oxide nanoparticles in environmental applications, such as remediation and sensing. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Superparamagnetic, iron oxide nanoparticle-based materials have been demonstrated to be excellent heavy metal sorbents owing in part to their high surface area per mass (> 100 m 2 g À1 ), their superparamagnetic properties that prevent magnetic agglomeration when dispersed, and that they can be easily removed from a sample system by applying an external magnetic field.…”
Section: Introductionmentioning
confidence: 98%
“…The sensitivity is not lower than that of complicated modified electrode 4,10,11,14,[29][30][31] or graphiteepoxy composite electrode. 9 Therefore, it is an attractive and very promising option for ultratrace metals analysis in seawater with two great advantages: the avoidance of harmful mercury and the avoidance of time-consuming procedures for pretreating water samples.…”
Section: Discussionmentioning
confidence: 99%
“…Their commonness is connected most of all to its simplicity and relatively high accuracy. There are many different types of voltammetric methods [7][8][9][10][11][12][13][14][15]. These methods differ from each other mainly in the voltage shape polarizing the voltammetric electrode, and in result, they also differ in accuracy of measurements conducted.…”
Section: Introductionmentioning
confidence: 99%